Use of natural rumen modulators to replace monensin plus virginiamycin in high-grain diets for cattle (Revista de Ciências Agroveterinárias, 2024)
This study aimed to evaluate food additives for the replacement of monensin and virginiamycin in high-grain diets for cattle. A Latin square experimental design was adopted, represented by four treatments (functional oil, yeast, tannin and control monensin and virginiamycin) in four experimental periods, with four animals cannulated in the rumen. l The natural ruminal modulators fully replaced the ionophores monensin and virginiamycin in the concentrate. Being evaluated: ruminal pH, apparent digestibility and in situ degradability of dry matter. The results showed that the pH variation curve as a function of rumen fluid collection time was not significant (P
Keywords: ruminants; additives; modulators